Concepts of human anatomy and physiology - Van De Graaf, Kent M.; Fox, Stuart Ira (Dubuque : W.C. Brown Co. Publisher, 1992)
This conceptual approach text is written in a clear style, with illustrations, tables that summarize and support textual information, colour-coded page indexing and "clinical investigations".
Orientation and organization of the human body -- Support and movement of the human body -- Integration and control systems of the human body -- Regulation and maintenance of the human body -- Continuance of the human species.
Includes bibliographical references (pages 889-893) and index.
Keywords: HUMAN ANATOMY